Assessing the ecological vulnerability of the upper reaches of the Minjiang River - Zhang, Jifei (PLoS One, 2017)
The upper reaches of the Minjiang River (URMR), located on the eastern edge of the Tibetan Plateau in southwestern China, are an important component of the ecological barrier of the Upper Yangtze River Basin. Climate change and human activities have increased the ecological sensitivity and vulnerability of the region, which may pose a threat to the ecological security of the Yangtze River Basin and have negative impacts on local social and economic development. In this study, we analyzed land use and cover change (LUCC) of the URMR between 2000 and 2010, and found that the total rate of LUCC was less than 0.50% during this period. In addition, net primary production (NPP) was employed to describe the changes in ecosystem sensitivity and vulnerability, and the results demonstrated that slightly and moderately sensitive and vulnerable zones occupied the largest area, distributed mainly in forest, shrub, and grassland ecosystems. However, compared with the period from 2000 to 2005, the ecological sensitivity and vulnerability showed a worsening trend in the period 2005–2010. Exploring the relationship between vulnerability/sensitivity and environmental factors, we found that sensitivity and vulnerability were positively correlated with precipitation (>700 mm) and aridity index (>36 mm/°C). The results highlight that the future ecological sensitivity and vulnerability of URMR should be further investigated, and that the LUCC induced by human activities and climate change have caused alteration of in ecosystem vulnerability.